Evaluation of Integrin Glycovariants as Biomarkers of Metastasis, Invasion, and Therapy Stratification in Head and Neck Squamous Cell Carcinoma - Erica Routila; Sadie Salminen; Randa Mahran; Mervi Toriseva; Heikki Irjala; Eeva Haapio; Eero Kytö; Sami Ventelä; Kim Pettersson; Johannes Routila; Kamlesh Gidwani; Janne Leivo (Cancer Medicine, 2025)
ABSTRACT Background Integrin glycosylation is one mechanism regulating the invasion and metastasis of malignant tumors. Little information exists about integrin glycosylation in head and neck squamous cell carcinoma (HNSCC). In this study, we evaluated the glycosylation of integrins in HNSCC tumor and serum samples. Methods Intraoperative fresh tumor and normal tissue samples and blood samples were collected from HNSCC patients (N = 24). Lectin‐bioaffinity assays using six nanoparticle‐bound lectins were used to evaluate the glycosylation of integrins ITGA2, ITGA3, ITGA5, ITGA6, ITGB1, and ITGB4. Associations with metastasis, therapy response, and clinical factors were analyzed. Results Glycosylation profiles of the integrins were relatively similar. High intratumoral ITGB1–WFL results were associated with high T class, whereas none of the integrin glycovariant assays provided significant resolution in the detection of nodal metastasis. While the serum integrin glycovariant levels were low overall, serum ITGA2–UEA offered significant resolution in both radiotherapy response prediction and cancer recurrence prognostication. Conclusions We demonstrate that while integrin glycovariants are abundant in HNSCC tumors and ITGB1‐WFL was associated with invasiveness, integrin glycovariants do not directly correlate with metastatic behavior. Further, serum ITGA2–UEA appeared as a potential radioresponse biomarker.